(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents a reactive impedance surface (RIS) and a defective ground surface (DGS) in a dual wideband planer inverted-F antenna (PIFA).DGS is a technique that allows tooptimize the antenna’s different parameters, like size reduction and bandwidth. The RIS structure, which consists of 3× 3 periodic metallic unit cells, aids in increasing the antenna’s bandwidth. The RIS PIFA using DGS to design, analyze, and execute antenna a 2.4 and 8.4 GHz. Finally, the complete 3D electromagnetic simulator HFSS used to simulate a prototype. The implemented results -10 dB < S11 impedance bandwidth design has estimated at being 1199 MHz (2.0734-3.26921GHz) 49.95% WLAN bands at 2.4 GHz and 912 MHz (8.0239-8.9321 GHz) 10.03% for X-bands at 8.4GHz.